The characterization and maternal phylogenetic analysis of complete mitochondrial genome of the native bian chicken - Bai, Hai; Liu, Limin; Zhang, Yongfang; Wen, Yuping; Zhang, Xing; Xiang, Hai (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Bian chicken (Gallus gallus, Linaeus, 1758) is an indigenous breed known for its unique traits that make it well-suited for rearing in the cold regions and highland hills of northern China. To better understand the genetic characteristics of this breed, we conducted high throughput sequencing to determine the complete mitochondrial genome (mitogenome) of the Bian chicken. The mitogenome of the Bian chicken was found to be 16,787 bp in size and consisted of 22 transfer RNA genes, 2 ribosomal RNA genes, 13 protein-coding genes, and 1 non-coding control region known as the D-loop. The overall nucleotide composition was found to be 32.45% C, 30.25% A, 23.8% T, and 13.5% G. Phylogenetic analysis showed that the Bian chicken is distantly related to the Zhuanghe big-boned chicken, but closely related to the Xiaoxiang chicken and Taoyuan chicken. This study not only provides valuable genetic data for the diversity and preservation of the Bian chicken breed, but also contributes additional evidence supporting the significantly different genetic relationship between the Bian chicken and the Zhuanghe big-boned chicken.